EFFECTS OF SOLID VINASSE-BASED ORGANIC FERTILIZER ON SOME GROWTH INDICES OF TOMATO PLANT - Kusumaningtyas, Ratna Dewi; Oktafiani, Oktafiani; Hartanto, Dhoni; Handayani, Prima Astuti (Jurnal Bahan Alam Terbarukan, 2017)
Vinasse, which is commonly referred to as stillage, is a aqueous by-product of bioethanol processing. This side-product is yielded in a very large quantity in bioethanol industry since the production of 1 L of ethanol will generate 13 L of vinasse. Hence it is become a problem of bioethanol industry since vinasse waste doesn’t have economic value and it is harmful to the environment. This industrial waste has high COD and BOD, high acidity, and high temperature when it is discharged from the bottom of distillation unit. To overwhelmed this drawbacks, it is crucial to attempt reduction of the negative characteristic of vinasse as well as creation of added value of vinasse. In fact, vinasse contains a considerable amount of potassium and organic matter which is beneficial for plant growth and improving the soil fertility. Thus, in this work, vinasse was utilized as raw material for organic fertilizer. Vinasse waste was formulated with other sugarcane industrial waste (filter cake and boiler ash), and NPK fertilizer in various composition to yield solid Organo-Mineral Fertilizer (OMF). Among all the composition of OMF, It was demonstrated that vinasse formulated with 3, 6, and 9% of NPK fulfilled the Indonesian National Standar (SNI) of solid fertilizer. Thus these types of OMF were used to fertilize tomato plant. The effects of vinasse-based OMF on some growth indices of tomato plant were examined. It was revealed that vinasse fertilizer formulated with 9% of NPK exhibited the best impact to the tomato plant growth.